Reconfigurable ultra wideband to narrowband antenna for cognitive radio applications using PIN diode - Aziz El fatimi; Seddik Bri; Adil Saadi (Universitas Ahmad Dahlan, 2020)
Frequency reconfigurable antennas are very attractive for many wireless applications.They offer many advantages such as simplicity and compactness. In this electronicpaper, we propose a reconfigurable antenna operating in the S and C bands. Theproposed antenna uses a BAP65-02 RF diode to switch between the ultra widebandfrom 2.92 to 6.19 GHz to the narrowband from 2.92 to 3.93 GHz. The ultra widebandis obtained by a partial rectangular ground plane with a symmetrical rectangular slotand the narrowband is obtained by adding a parasitic element electrically connectedto the ground plane by the PIN diode when it is positively biased. This patch antennaoperates in the Federal Communications Commission band (FCC) and can be used forbiomedical applications such as radiometry imaging. The numerical simulation resultsbased on the finite element method and the finite integral method show a very goodagreement between them.